A comparative investigation on mechanical strength of blended concrete with surface modified rubber by chemical and non-chemical approaches - M.N., Noor Azline; A.B., Nabilah; S., Nor Azizi; A.A., Farah Nora Aznieta (Elsevier, 2022)
Tremendous efforts have been made to improve the bonding characteristics between rubber particles and the cement matrix using surface treatment of the rubber. This study is designed experimentally to explore the significance of rubber surface treatment by chemical and non-chemical approaches. The finding is also expected to evaluate the significance of the combining methods in improving the rubberized concrete’s behavior and aims to evaluate the sustainable aspect of promoting the rubberized concrete for practical application in industry. A total of 10% of treated rubber and 15% of metakaolin were used to replace fine aggregate and cement, respectively. Two surface treatment methods were applied, namely (1) a non-chemical approach by water soaking treatment with cement coating and (2) a chemical approach using sodium hydroxide (NaOH) solution soaking treatment. A comparable compressive strength was observed due to the improvement of the interfacial gap in the rubberized concrete. Results show that the compressive strength of rubber with water-cement coated (WCC) and NaOH treatments (NaOH) is 44.4 N/mm2 and 46.4 N/mm2, respectively. The study found that there was no significant difference in the mechanical strength of rubberized concrete using the two surface treatment methods. A similar behavior was also observed in the energy absorption capability of rubberized concrete, where the surface treatments did not significantly affect the property of treated rubberized concrete. Overall, the finding suggests that the combining method between rubber surface treatment and cement blended enhances the properties of rubberized concrete and has potential for concrete structural elements. Furthermore, the environmental assessment revealed a significant reduction in the embodied CO2 of rubberized concrete compared to 100%OPC concrete. However, the cost for rubberized concrete production was slightly higher than for non-rubberized concrete. Nevertheless, it was found that the surface treatment methods were easy and practical for application in the construction industry.